1996
DOI: 10.1346/ccmn.1996.0440101
|View full text |Cite
|
Sign up to set email alerts
|

Berthierine from the Lower Cretaceous Clearwater Formation, Alberta, Canada

Abstract: Abstract--Berthierine occurs as pore-linings of well crystallized laths of variable thickness in oil-sands of the Clearwater Formation, Alberta, Canada. Berthierine crystallized early in diagenesis within portions of a deltaic/estuarine complex dominated by brackish to fresh water.Separates prepared using high gradient magnetic separation contain approximately equal amounts of monoclinic and orthohexagonal berthierine. Minor, but variable, quantities of inseparable, iron-rich impurities mainly consist of chamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 70 publications
1
63
0
1
Order By: Relevance
“…Hornibrook and Longstaffe (1996) have shown that berthierine crys tal lised at a tem per a ture of 25-45°C. Accord ing to Worden and Morad (2003) and Wil son (2013) the forma tion of berthierine took place in trop i cal, off shore and deltaic en vi ron ments where iron-bear ing fresh wa ter mixed with sea wa ter.…”
Section: Origin Of Berthierinementioning
confidence: 99%
See 3 more Smart Citations
“…Hornibrook and Longstaffe (1996) have shown that berthierine crys tal lised at a tem per a ture of 25-45°C. Accord ing to Worden and Morad (2003) and Wil son (2013) the forma tion of berthierine took place in trop i cal, off shore and deltaic en vi ron ments where iron-bear ing fresh wa ter mixed with sea wa ter.…”
Section: Origin Of Berthierinementioning
confidence: 99%
“…Its chem ical com po si tion is iden ti cal to that of iron-rich leptochlorite, com monly re ferred to as chamosite. It may also be sim i lar to the com po si tion of an other iron alu mi no sili cate -odinite (Hornibrook and Longstaffe, 1996). Berthierine (like chamosite) is gen er ally con sid ered to be char ac ter is tic of ma rine de pos its (Tay lor and Curtis, 1995;Ryan and Hill ier, 2002;Tay lor et al, 2002), al though it has also been re ported in de pos its of brackish bas ins (Tay lor, 1990), in laterites (Fritz and Toth, 1997), and even in hy dro ther mal de pos its (Rivas-Sanchez et al, 2006).…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…7). Acredita-se que a chamosita presente nesses arenitos seja produto de uma provável transformação isoquímica mesodiagenética da bertierina (Hornibrook & Longstaffe 1996;Morad et al 2000;Velde 2003), em temperaturas em torno de 120-160ºC (Curtis 1985).…”
Section: Figura 6 -Diferentes Aspectos Petrográfi Cos Dos Ooides De Bunclassified